ARGUMENTASI HASYIM ASY’ARI DALAM PENETAPAN AHLUS SUNNAH WAL JAMA’AH SEBAGAI TEOLOGI NAHDLATUL ULAMA - Ahmad Choirul Rofiq (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
Nahdlatul Ulama, established on January 31, 1926, has affirmed his attitude of Ahlus Sunnah wal Jama'ah (Aswaja) by following al-Ash'ari and al-Maturidi. However, until now there has not been a comprehensive study of the arguments that form the backdrop of the theological decisions, but this issue is very urgent to find the answer. Everyone acknowledged the character, keulamaan, and heroism of KH Muhammad Hasyim Asy'ari. This paper describes the gait of the founder of Pesantren Tebu Ireng and also the Founding Fathers of Nahdlatul Ulama in defending Aswaja and analyzing the motivation behind it by using the theory of action motif according to Weber's perspective. By reviewing his works collected in Irshad al-Sary fi Jam 'Mushannafat al-Shaykh Hashim Ash'ari, it can be stated that KH Hasyim Asy'ari's argument for choosing Aswaja is his belief in the truth of Aswaja as the most surviving Islamic school of madhhab -the other theological ideology, Aswaja's position as al-sawad al-a'zham (the majority school of Muslims), and his understanding that maintaining Aswaja is a duty of the Muslims. Thus, the motivation tends to be based on religious values ​​in order to achieve goals according to normative idealism. The success of KH Hasyim Asy'ari in strengthening Aswaja with its moderating characteristics in Indonesia should be continued by Indonesian Muslims to be role models in promoting moderate and tolerant Islam.